2011
DOI: 10.1111/j.1467-8543.2011.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Management, Organizational Justice and Emotional Exhaustion among Chinese Migrant Workers: Evidence from two Manufacturing Firms

Abstract: This article explores how Human Resource (HR) policies and practices influence employee perceptions of organizational justice, which in turn impacts employee emotions and feelings of emotional exhaustion. Using structural equation modelling and based on employee survey data drawn from two manufacturing organizations, we find that a strong HR system -perceived by workers as distinctive, attractive and consistently implemented -fosters perceptions of distributive, procedural and interactive justice. However, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 64 publications
4
70
1
1
Order By: Relevance
“…In the case of these Chinese managers, feelings of exhaustion are more sensitive to perceived pay equity than they are to the absolute level of pay. This finding parallels that of Frenkel, Li and Restubog () who found that distributive justice was the strongest predictor of negative emotions and exhaustion among 364 Chinese workers in two cosmetic manufacturing companies. In terms of other cross‐links, we did not confirm a relationship between job demands (problem‐solving demands and role overload) and engagement (hypotheses 5 and 6).…”
Section: Discussionsupporting
confidence: 87%
“…In the case of these Chinese managers, feelings of exhaustion are more sensitive to perceived pay equity than they are to the absolute level of pay. This finding parallels that of Frenkel, Li and Restubog () who found that distributive justice was the strongest predictor of negative emotions and exhaustion among 364 Chinese workers in two cosmetic manufacturing companies. In terms of other cross‐links, we did not confirm a relationship between job demands (problem‐solving demands and role overload) and engagement (hypotheses 5 and 6).…”
Section: Discussionsupporting
confidence: 87%
“…Supporting this theory's assertion, previous studies report that insufficient rewards and lack of recognition decreases employees' resilience to burnout (Chappell & Novak, 1992;Maslanka, 1996). More specifically, it is reported that individuals who have experienced an imbalance in efforts and rewards are more likely to feel emotionally exhausted than those who have not (Bakker, Kilmeri, Sigrist, & Schaufeli, 2000;Frenkel, Li, & Restubog, 2012). Therefore, we propose that academicians experiencing a discrepancy between their efforts and outcomes are more likely feel emotionally exhausted.…”
Section: Areas Of Worklife and Emotional Exhaustionsupporting
confidence: 54%
“…In this type of context, the key mechanism may be management practices that promote collective activities, rituals and ceremonies, and hence encourage organizational identification rather than HR practices that foster procedural and distributive justice. Over time, however, we would expect issues of organizational justice to become more salient as is evident in the more industrialized areas of China (Frenkel, Li and Restubog 2012). Clearly, this is a matter for further research.…”
Section: Discussionmentioning
confidence: 88%